Enhancing the Uniformity of Emitter Air Bubble Delivery During Irrigation With Aerated Water - Manouchehr Torabi; Mokhtar Miranzadeh (مهندسی منابع آب, 2021)
Introduction: Oxygation is a variant of subsurface drip irrigation in which ambient air is injected through the system via a venturi, thereby plant roots receive air and water simultaneously. The objective of this research was to study the effect of two surfactants and certain ratios of them on the uniformity distribution of emitter air flow rates along lateral pipes in an oxygation system. Matherials and Methods: Two non-ionic surfactants, namely, Triton X-100 and Tween 80, and three mixtures of them with different ratios including 2:1, 1:1, and 1:2 were added to irrigation water and the results were compared to the case where no surfactant was used. For statistical analysis of data, the Kolmogorov–Smirnov and Friedman tests along with Christiansen Uniformity Coefficient were used. Findings: In the absence of surfactants, Christiansen uniformity coefficient (CUC) for emitter air flow rates was -67 percent. The relative increase in CUC, when Triton X-100, Tween 80, and the ratios 2:1, 1:1, and 1:2 were applied, amounted to 211, 162, 210, 213, and 206 percent, respectively. Conclusion: The results of this research clearly indicates that application of surfactant mixtures with synergic interaction will effectively enhance distribution uniformity of emitter air flow rates.